Roger Sheringham and the vane mystery : a Roger Sheringham case - Berkeley, Anthony, 1893-1971 (Roger Sheringham Cases, 2003)
A Roger Sheringham mystery from Golden Age author Anthony Berkeley When the Daily Courier sends Roger Sheringham to Hampshire, it's a job after his own heart.The body of a woman has been found at the bottom of the cliffs at Ludmouth Bay, and despite a verdict of accidental death, the local sighting of Inspector Moresby from Scotland Yard suggests otherwise.Unable to resist a little amateur sleuth work, Sheringham starts digging around.Events lead him down one blind alley after another as he attempts to rival Inspector Moresby and devise the correct theory about the tragic death of Mrs Vane.